Protein Kinase Ime2 Is Required for Mycelial Growth, Conidiation, Osmoregulation, and Pathogenicity in Nematode-Trapping Fungus Arthrobotrys oligospora - Xie, Meihua (Front Microbiol, 2020)
Inducer of meiosis 2 (Ime2), a protein kinase that has been identified in diverse fungal species, functions in the regulation of various cellular processes, such as ascospore formation, pseudohyphal growth, and sexual reproduction. In this study, AoIme2, an ortholog of Saccharomyces cerevisiae Ime2, was characterized in the nematode-trapping fungus Arthrobotrys oligospora. Disruption of the gene Aoime2 caused defective growth, with slower mycelial growth in ΔAoime2 mutants than the wild type (WT) strain, and in the mutants, the number of hyphal septa in mycelia was higher and the number of cell nuclei in mycelia and conidia was considerably lower than in the WT strain. The conidial yields of the ΔAoime2 mutants were decreased by ∼33% relative to the WT strain, and the transcription of several sporulation-related genes, including abaA, fluG, rodA, aspB, velB, and vosA, was markedly downregulated during the conidiation stage. The ΔAoime2 mutants were highly sensitive to the osmotic stressors NaCl and sorbitol, and the cell wall of partial hyphae in the mutants was deformed. Further examination revealed that the cell wall of the traps produced by ΔAoime2 mutants became loose, and that the electron-dense bodies in trap cells were also few than in the WT strain. Moreover, Aoime2 disruption caused a reduction in trap formation and serine-protease production, and most hyphal traps produced by ΔAoime2 mutants did not form an intact hyphal loop; consequently, substantially fewer nematodes were captured by the mutants than by the WT strain. In summary, an Ime2-MAPK is identified here for the first time from a nematode-trapping fungus, and the kinase is shown to be involved in the regulation of mycelial growth and development, conidiation, osmolarity, and pathogenicity in A. oligospora.